2013
DOI: 10.12968/bjon.2013.22.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Role modelling and students' professional development

Abstract: Patients expect to be cared for by nurses who are not only competent but also behave professionally, so students must be educated to develop professional qualities. The Nursing and Midwifery Council stipulates that professional values must underpin education as well as practice (NMC, 2010a). Much has been written on the qualities of an effective role model and the potential barriers to becoming one. This article focuses on preregistration adult nursing education and role modelling, with a slant towards the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
1
29
1
Order By: Relevance
“…Likewise, there is a need for greater understanding and preparation on how to initiate and maintain a professional relationship that contributes to a quality learning experience. This reinforces the need for nurse academics within the tertiary environment as initial role-models to students (Felstead, 2013) to facilitate an early understanding of working with the SWN. Improved understanding would help to better prepare students for practice and encourage them to draw from the experiences of working with SWNs in order to facilitate a quality PEP.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Likewise, there is a need for greater understanding and preparation on how to initiate and maintain a professional relationship that contributes to a quality learning experience. This reinforces the need for nurse academics within the tertiary environment as initial role-models to students (Felstead, 2013) to facilitate an early understanding of working with the SWN. Improved understanding would help to better prepare students for practice and encourage them to draw from the experiences of working with SWNs in order to facilitate a quality PEP.…”
Section: Discussionmentioning
confidence: 53%
“…Improved understanding would help to better prepare students for practice and encourage them to draw from the experiences of working with SWNs in order to facilitate a quality PEP. It has been suggested that if students are educated and advised in advance on what to expect during PEP, they can be more observant of SWN behaviours and attitudes (Felstead, 2013). This can lead to an improvement in the expectations of the relationship between the student and the SWN with the mutual understanding that the patients' needs come first (Paton, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Felstead (2013) concurs that patients expect to be cared for by nurses who are competent but also act professionally. Keeling & Templeman (2013) assert that student nurses can feel vulnerable as they are aware of their increasing responsibility and the professional implications associated with this.…”
Section: Discussion From Findings Accountability and Responsibilitymentioning
confidence: 99%
“…Accountability is an integral part of professional practice, Felstead (2013) suggests that both clinical and academic staff are able to exemplify behaviours and attitudes that influence the development of professionalism in student nurses. Nurses are expected to make clinical judgements in a wide variety of areas of practice on a daily basis.…”
Section: Discussion From Findings Accountability and Responsibilitymentioning
confidence: 99%
“…The professional identity of student nurses may fluctuate or even disintegrate when exposed to clinical realities in recognizing the nursing profession. A self-identity must be integrated firstly with new expectations and modified within a social context to form a professional identity (Felstead, 2013).…”
Section: Relevant Scholarshipmentioning
confidence: 99%